Anatomy of a friendship : a dual memoir of women's journeys through war to peace - Spiegel, Cecile, 1915-2010; Tuckman, Diane, 1935- (Cherry Orchard Books, an imprint of Academic Studies Press, 2022)
"Diane Tuckman and Cecile Spiegel fled religious persecution with WWII conflicts at their heels. Separately, from Egypt and from Germany, each leaped continents, cultures, and languages as a refugee before finding a new home in the United States. Hiding in plain sight in France, Cecile eluded capture by the Nazis, but lost many dear to her. Diane came of age there, far from the Mediterranean idyll of her childhood in Egypt. They relied on family, faith, and resilience to overcome the otherness felt by displaced peoples. As they dictated their memoirs to one another, Diane and Cecile discovered the anatomy of their friendship in their parallel odysseys and the optimism of 20th century American womanhood"--